2012
DOI: 10.1099/jmm.0.047027-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characteristics of Korean Beijing Mycobacterium tuberculosis strain K1 in an aerosol challenge model and in the Cornell latent tuberculosis model

Abstract: The Beijing Mycobacterium tuberculosis family is widely distributed and is the most common M. tuberculosis strain in East Asia. The highly transmissible and predominant Beijing M. tuberculosis strain in Korea, M. tuberculosis K1, was characterized using an aerobic challenge mouse model and a latent tuberculosis model with M. tuberculosis H37Rv as a reference. M. tuberculosis K1 multiplied over ten times more rapidly than M. tuberculosis H37Rv during the early stage of infection and induced high levels of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…The Mtb K strain phylogenetically belongs to the Beijing genotype; it was most widely isolated in an outbreak of pulmonary TB in senior high schools in South Korea [ 21 ]. Importantly, our previous study showed that Mtb K replicated rapidly during the early stages of infection in a murine model of TB with a more severe pathology [ 22 ]. During the study, intriguingly, we observed that there was only a small colony forming unit (CFU) difference at later time points (> 12 weeks post-infection) between the K strain and H37Rv, but the K strain led to death earlier than H37Rv because of an excessive host immune response [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Mtb K strain phylogenetically belongs to the Beijing genotype; it was most widely isolated in an outbreak of pulmonary TB in senior high schools in South Korea [ 21 ]. Importantly, our previous study showed that Mtb K replicated rapidly during the early stages of infection in a murine model of TB with a more severe pathology [ 22 ]. During the study, intriguingly, we observed that there was only a small colony forming unit (CFU) difference at later time points (> 12 weeks post-infection) between the K strain and H37Rv, but the K strain led to death earlier than H37Rv because of an excessive host immune response [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beijing/K strains were identified as the major cause of pulmonary TB outbreaks (14) and were associated with drug resistance (13) in South Korea. The Beijing/K strain has rapid replication with more severe pathologies at early times after infection compared to M. tuberculosis H37Rv in mice (15,16).…”
mentioning
confidence: 99%
“…M. tuberculosis K replicates rapidly during the early stages of infection in a murine model of TB, causing a more severe pathology and a high level of reactivation from latent infection [ 14 ]. In addition, the Bacillus-Calmette-Guérin vaccination is less effective against an M. tuberculosis K infection than H37Rv T (unpublished data).…”
Section: Introductionmentioning
confidence: 99%